SISTEM INFORMASI AKUNTANSI PENJUALAN PAKAIAN BERBASIS WEB DI KONVEKSI GARMENESIA - Sindi Ega Yagusmiadihatna; Nur Annisa; Candra Mecca Sufyana (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
AbstractThe development of information technology is one of the competitive factors in the business world that the company or business people are competing to get customers and inform their sales by selling online using the website. E-commerce is the transaction of buying and selling goods and services through electronic systems such as the internet. This study aims to find out and find solutions to the constraints that exist in the current sales accounting information system. According to observations and interviews that the author did, Garmenesia convection often experiences problems in the sales system, whether it's difficulties in archiving documents, unstructured sales reports, damage, and loss of files due to the system still being done manually. This research uses a method of observation, interviews, literature study, analysis, design of information systems, continued with system development and the testing author gets the results, namely an E-commerce-based Sales Accounting Information System. Garmenesia convection requires an online store or website, makes a solution to minimize the problem in data collection or sales reports, and maximizes service to a customer.Â Keywords: Sales, website, information system